Complementarity With the Principles of Subsidiarity and Proportionality in the Area of Freedom, Security and Justice - Tudor, Andreea-Loredana (Acta Universitatis Danubius. Relationes Internationales, 2025)
The European Union is the guarantor of 27 different visions in the field of security and respect for human rights. The European idea has endured for more than 70 years, and the numerous transformations it has undergone, reforms and the integration process are the result of permanent adaptation to the surrounding reality, as well as the will of its equal members. Sovereignty is an internationally recognised and promoted principle, and one of the basic principles of the EU is its recognition of Member States. However, the issue of sovereignty seems to be increasingly threatened by EU policies. Even if the EU acts only within the sphere of shared competences, based on the principle of subsidiarity and proportionality, the policy on the area of freedom, security and justice reveals the most sensitive area of conflict on the issue of sovereignty and respect for human rights. This paper aims to analyse, including from the perspective of the impact of international conflicts, the effects of decision-making at the EU level on the area of freedom, security, and justice policy, and the effectiveness of bringing this policy within the sphere of shared competences between the EU and its Member States. Ultimately, this analysis seeks to address the question of the need for reform of the existing EU treaties, particularly in the areas of civil, criminal, and police cooperation.